Assessment of Body Posture of Children With Chest Pain - Zmyślna, Anna; Żurawski, Arkadiusz Łukasz; Śliwiński, Grzegorz; Śliwiński, Zbigniew Włodzimierz; Kiebzak, Wojciech Piotr (Frontiers in Pediatrics, 2021)
Abstract Objective: An increase in the appearance of chest pain among children is observed globally. The authors present various reasons for their appearance. As can be seen from numerous observations, the majority of cases are not related to the pathology of the circulatory system. Increasingly, studies on the causes of chest pain in children show their association with musculoskeletal disorders. Aim of the work was assessment of body posture in children with chest pain using the Diers Formetric 4D system. Methods: The study involved a group of 184 female and male children, aged 7-12 years. The study group consisted of 64 patients with chest pain. The children from this group were diagnosed with functional chest pain by a cardiologist. The control group consisted of 120 patients without chest pain. The study included the assessment of body posture using the DIERS Formetric system. Results: The analysis of the results obtained during the study showed that among the children with chest pain, there are statistically significant irregularities in the parameters determining body posture compared to the control group. Comparing the study group with the control group, there is a statistically significant difference in the lateral deviation of VPDM (rms) [mm] (p = 0.001). Both children from the test group aged 9-10 and 11-12 obtained higher results than their peers from the control group. In the group of the youngest children in terms of the lateral deviation of VPDM (rms) [mm], increasing the number of children under study would contribute to significant differences in this variable.In the study group, among children aged 9-10 years, there were also statistically significant abnormalities regarding trunk imbalance and pelvic skewness compared to the children of the same age in the control group. Conclusions: Irregularities in the parameters determining body posturę may cause chest pain in children.